Phenological responses of Brazilian wheat cultivars to vernalization and photoperiod - Ribeiro, Tanaka Lima Parreira; Cunha, Giberto Rocca da; Pires, João Leonardo Fernandes; Pasinato, Aldemir (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the effects of vernalization and photoperiod on the phenological development of five Brazilian wheat cultivars. The experiment was carried out in Passo Fundo, Rio Grande do Sul state, Brazil, in three sowing dates: June 23, July 25 and August 27 of 2003. The experimental design was random block, with split split plots, and four repetitions. The treatments consisted of: three light regimes – natural photoperiod (NP), four hour day length extensions (EP 4), and an extended photoperiod of 20 hours of light per day (EP 20), in the main plot; two vernalization regimes – unvernalized (NV) and vernalized during thirty days (V) – in the split plot; and five wheat cultivars – BRS 179, BRS 194, BRS 207, BRS Figueira, and BRS Umbu – evaluated in the split split plots. There was an interaction between photoperiod and cultivar cycle for the first sowing date. For all the cultivars, the cycle was reduced with the increase of the photoperiod. However, for the second and third sowing dates, there was also an interaction between cultivars and vernalization. These variables accelerated the crop cycle, and affected the duration of important subperiods for the composition of yield grain components.